Dalbavancin for infective endocarditis: A systematic review of effectiveness, safety, and dosing - Anastasios E Chaldoupis; Vasilios Petrakis; Petros Ioannou; Konstantina A Tsante; Deny Tsakri; Aglaia Domouchtsidou; Stella Baliou; Marianna Vlachaki; Alexandra Mpakosi; Sotirios P Fortis; George Samonis; Rozeta Sokou; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Infective endocarditis (IE) requires prolonged intravenous antibiotic therapy, leading to extended hospitalization and increased morbidity. Dalbavancin, a long-acting antibiotic with excellent tissue penetration and a favorable safety profile, can be a promising alternative. This systematic review aimed to investigate the current literature regarding the use of dalbavancin for infective endocarditis. Methods A systematic search of PubMed and Scopus was conducted according to PRISMA guidelines. Eligible studies included adult patients (≥ 18 years) with IE diagnosed by the modified Duke criteria, treated with dalbavancin as monotherapy or sequential/consolidation therapy. Data extraction included demographics, type of IE, causative pathogen, dosing regimen, surgical intervention, adverse events, and outcomes. Descriptive analyses were performed. Results Thirty-eight studies including 565 patients were analyzed. The overall cure rate was 88.0%, with a similar success rate across native valve (90.1%), prosthetic valve (90.0%), and cardiac device-related IE (86.0%). Staphylococcus aureus , Coagulase-negative staphylococci (CNS), Streptococcus spp ., and Enterococcus faecalis were the most common pathogens. Cure rates were comparable among most pathogens, though a lower cure rate was evident in infections due to Enterococcus faecalis compared to Streptococcus spp. (80.7% vs. 96.6%, p = 0.008). An effective antimicrobial exposure of 2 weeks had similar success rate compared to a longer period of effective antimicrobial exposure ( p = 0.31). Adverse events were rare (2.9%), with mild rash being the most common. Conclusions Dalbavancin demonstrates high cure rates and excellent tolerability in IE, and could offer an attractive alternative to conventional prolonged intravenous therapy. Further randomized controlled trials are warranted to define standardized protocols.